Community Empowerment Through Healthy Kitchens Overcomes Stunting Towards Stunting-Free Villages: Pemberdayaan Masyarakat Melalui Dapur Sehat Atasi Stunting Menuju Desa Bebas Stunting - Mutiara, Erli; Hasibuan , Novita Indah; Yunita , Sri; Saleh, Khaerul; Akmal, Nikmat (Universitas Lancang Kuning, 2024)
Stunting is one of the health problems that is still prevalent in Indonesia. The problem of stunting is a concern for all government officials, from ministries to village heads. Regional Partnership Service Partners (PKW): Head of Pagar Jati Village and Village Midwife. The problem faced by the Head of Pagar Jati Village is that toddlers are categorized as stunting. The objectives of PKW: (1) to conduct socialization of stunting prevention, utilization of local food and understanding of nutrition; (2) training and assistance in preparing healthy and hygienic menus from local food sources, as well as practicing processing local food for family menus. The method of implementing PKW is through: socialization, training, and assistance. The results of the activity show that the community empowerment strategy through the DASHAT program has been implemented in accordance with the empowerment concept by the Unimed PKW team. It is hoped that mothers will have strong motivation in meeting toddler nutrition and improving mothers' attitudes and actions in providing balanced nutrition to stunted toddlers. So that Pagar Jati Village, Lubuk Pakam District, Deli Serdang Regency can be free from Stunting.